PENGENDALIAN STRES PADA WANITA (TINJAUAN DARI PEKERJAAN DAN STATUS GIZI) - Endang Mulyatiningsih (Jurnal Penelitian Humaniora, 2000)
Abstract This study was aimed to (1) find out the difference between the stress control of woman who worked as civil servants, who worked in the private sector and who worked  as civil servants, who worked in the private sector and who were housewives, (2) compare the stress control among women having the nutritional status of underweight, ideal-weight, and overweight. The research population was all women of 30 to 50 year’s old living in Sleman district. The sample was drawn using the multistage, stratified and purposive sampling technique. The data were collected by using a questionnaire with the total sample size was 270 subjects. The data were analyzed by utilizing the one-was Anova, followed by Duncan’s Multiple Range Test. The findings of the study showed that there was a different in the stress control between the women who worked in civil servants, in private sector, and as housewives with F ratio=3.57 (p=0.03). There was a significant difference in the stress control between the women having the nutritional status of the underweight, ideal-weight and overweight with F ratio= 21.174 (p=0.00). Further analysis showed that women who worked as civil servants had better ability to control stress than those who worked in the private sector. There was no significant difference between the women who were housewives and those who worked as civil servants and those who worked in private sector. Further analysis in the variable of nutritional status showed that the women having the nutritional status of ideal-weight and overweight had a better stress control than those having nutritional status of underweight.